Analysis of Factors Affecting Repurchase Intentions with Purchasing Decisions as Mediating Variables - Satoto, Eko Budi (Universitas Bina Sarana Informatika, 2024)
This study seeks to examine the factors influencing repurchase intentions, with a focus on purchasing decisions as a mediator. Using Smart PLS version 3.0 and a quantitative approach, the research involves Mie Gacoan Jember customers as the population, with 200 respondents selected through purposive sampling. Data collection involves a Likert Scale questionnaire. The results reveal that Store Atmosphere and Promotional Media Through Instagram significantly and positively impact purchasing decisions, while Product Variety does not. However, Store Atmosphere and product variety have a negative and insignificant effect on Repurchase Intention, contrasting with the positive impact of promotional interest through Instagram and purchasing decisions on Repurchase Intention. Purchasing decisions do not mediate the relationship between Store Atmosphere and product variety on Repurchase Intention but do mediate the effect of promotional interest through Instagram. The study's theoretical contribution provides insights for companies and researchers to enhance understanding of improving purchasing decisions and customer loyalty in physical stores and through social media promotions. Practical implications suggest that companies should enhance store atmosphere and Instagram promotions to boost purchasing decisions and repeat purchases, emphasizing the limited impact of product variety. The study acknowledges limitations and recommends future research to explore additional variables influencing consumer behavior.